Qualitative Study of Spiritual Experiences in Nurses of Psychiatry Wards - Mojtaba Haghanizemeydani; Sedigheh Ahmadi; Firozeh Ashouri; Esmaeil Showani; Leila Monavari Roozbahani (Kerman University of Medical Sciences, 2020)
Introduction: Seeking meaning and purpose can affect the quality of the nurses' caring for patients. The process of this meaning seeking is rooted in the value system of nurses. The present study aims to investigate the lived experience of spirituality among nurses working in Razi psychiatric Hospital, Tehran, in 2017. Methods: The present study is a qualitative study which is conducted by content analysis method. The study population consisted of the, nurses working in Razi Psychiatric Hospital. The participants were selected based on purposeful sampling... Thee sampling continued until the data were saturated (13 individuals). The data collection was conducted by in-depth semi-structured interviews which were recorded and all the contents were written down word by word. For analyzing the data, the qualitative content analysis method was used, in which similar data were organized and coded in similar categories. Results: Approximately 1000 statements and sentences were obtained as meaning units, Finally, 4 main codes and 16 open codes were extracted. The main themes included: "sacred profession, worship services, humanitarian tendencies, mission and purpose (meaning) in life. Conclusion: Participants of the study, e.g. nurses, considered spirituality as an inseparable part of their profession. In terms of their spiritual experience, respectively, holy profession, worship services, humanitarian tendencies, mission and purposefulness (meaning) in life,were considered as five most important experiences.